Genome-wide association study reveals quantitative trait loci for waterlogging-triggered adventitious roots and aerenchyma formation in common wheat - Xu, Le; Zhao, Chenchen; Pang, Jiayin; Niu, Yanan; Liu, Huaqiong; Zhang, Wenying; Zhou, Meixue (Frontiers in Plant Science, 2022)
Waterlogging severely affects wheat growth and development. Limited availability of oxygen in the root zone negatively affects the metabolism of plants. The formation of adventitious roots (ARs) and root cortical aerenchyma (RCA) are the most important adaptive trait contributing to plants’ ability to survive in waterlogged soil conditions. This study used a genome-wide association study (GWAS) approach with 90K single nucleotide polymorphisms (SNPs) in a panel of 329 wheat genotypes, to reveal quantitative trait loci (QTL) conferring ARs and RCA. The wheat genotypes exposed to waterlogging were evaluated for ARs and RCA in both field and glasshouse over two consecutive years. Six and five significant marker-trait associations (MTAs) were identified for ARs and RCA formation under waterlogging, respectively. The most significant MTA for AR and RCA was found on chromosome 4B. Two wheat cultivars with contrasting waterlogging tolerance (tolerant: H-242, sensitive: H-195) were chosen to compare the development and regulation of aerenchyma in waterlogged conditions using staining methods. Results showed that under waterlogging conditions, H2O2 signal generated before aerenchyma formation in both sensitive and tolerant varieties with the tolerant variety accumulating more H2O2 and in a quicker manner compared to the sensitive one. Several genotypes which performed consistently well under different conditions can be used in breeding programs to develop waterlogging-tolerant wheat varieties.